2018
DOI: 10.1111/jocn.13987
|View full text |Cite
|
Sign up to set email alerts
|

Roles and functions of enrolled nurses in Australia: Perspectives of enrolled nurses and registered nurses

Abstract: Health service providers, policymakers and education providers need to work collaboratively to ensure that facets of enrolled nurse education and scope of practice in line with regulation are affirmed by all concerned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…ENs in Healey and Reeds' (2015) study considered their role to be similar or the same of that an RN but that continued debate around scope of practice had led to confusion and discrimination. These findings are supported by recent research that demonstrates RNs' and managers' perceptions of the role are at odds to that of ENs (Endacott et al, 2018;Lavander, Suhonen, Turkki, & Merilainen, 2018). Perhaps significantly in terms of retention mature-aged ENs were more able to accurately identify which nursing tasks were the domain of the EN (Lavander et al, 2018).…”
Section: Discussionsupporting
confidence: 70%
“…ENs in Healey and Reeds' (2015) study considered their role to be similar or the same of that an RN but that continued debate around scope of practice had led to confusion and discrimination. These findings are supported by recent research that demonstrates RNs' and managers' perceptions of the role are at odds to that of ENs (Endacott et al, 2018;Lavander, Suhonen, Turkki, & Merilainen, 2018). Perhaps significantly in terms of retention mature-aged ENs were more able to accurately identify which nursing tasks were the domain of the EN (Lavander et al, 2018).…”
Section: Discussionsupporting
confidence: 70%
“…This is consistent with other studies (Geraci & Thigpen, ; L'Ecuyer, Hyde, & Shatto, ; Sambunjak, Straus, & Marusic, ). For example, most enrolled nurses (ENs) receive lower levels of education than advanced practice nurses (APNs) (Endacott et al, ; Harbman et al, ), but the work of ENs is increasingly complex when they provide direct care to residents and are involved in an educational role (Gibson & Heartfield, ). ENs can also be chosen as mentors.…”
Section: Discussionmentioning
confidence: 99%
“…Eight factors were reported in the included studies as influencing scope of practice. These were education [ 15 , 36 – 49 ], competency [ 15 , 36 – 38 , 41 44 , 46 , 47 , 50 ], professional identity [ 36 , 51 , 52 ], role confusion [ 15 , 37 , 39 , 42 , 44 ], legislation and regulatory policies [ 47 , 50 , 53 , 54 ], organisational structure [ 36 – 38 , 42 , 44 , 46 , 55 ], financial factors [ 36 , 37 , 41 , 42 , 44 48 , 52 , 56 , 57 ], and professional and personal factors [ 48 , 52 ]. The factors identified in the literature have been reported verbatim, without interpretation or modification.…”
Section: Resultsmentioning
confidence: 99%
“…Several papers identified pre- and post-professional education as an enabler and/or barrier to scope of practice [ 15 , 42 , 43 , 46 , 47 , 53 , 58 ]. For example, Brown et al [ 53 ] and Endacott et al [ 39 ] found that when an enrolled nurse (EN) with a diploma-level qualification [ 59 ] completed post-professional education to transition to registered nurse (RN) (bachelor’s degree) [ 60 ], their scope of practice significantly increased. Their new responsibilities included undertaking wide-ranging patient assessment; developing a nursing care-plan in consultation with the multidisciplinary team and assessing the outcome; and administering medications and assessing the outcome.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation